What's in a Name? - An ethnical discrimination experiment - Håkan J. Holm (Lund University, School of Economics and Management, Department of Economics, 2001)
This paper presents the results from an ethnical discrimination experiment that was conducted in one of Sweden's most "problematic" cities with respect to the integration process of refugees. The subjects confronted three different bargaining games; one trust game, one social exclusion and coalition formation game; and one battle of the sexes game. No general discrimination effect was detected. However, one specific effect was that Non-Swedes were less likely to be chosen as bargaining partners in the coalition formation game. Another specific effect was found in the males' trust and ultimatum responses; Non-Swedes had higher returns on being generous compared to Swedes.
Keywords: C78; C91; J71; 330; bargaining; ethnical discrimination; experiments